A Cross-National Multilevel Analysis of Fear of Crime: exploring the Roles of Institutional Confidence and Institutional Performance - Lin, Kai (Crime & delinquency, 2023)
Drawing upon Wave 7 of the World Value Survey, this study performed multilevel analysis on fear of crime among 47,996 residents from 36 diverse nations. Confidence in the government and perceived government performance were identified as significant predictors of crime fear. Further analysis showed the effect of confidence in the government stemmed primarily from between-country variation, whereas both within-country and between-country variation in perceived government performance shaped fear of crime. In addition, macroeconomic factors and the proportion of urban population, but not national-level homicide rate, were found to be salient country-level predictors. The findings contextualize the elevated fear of crime in some countries despite declining crime rates and inform the recommendation that institutional confidence and performance be prioritized in crime fear reduction efforts.